STUDI KASUS PENERAPAN TERAPI KELOMPOK TERAPEUTIK DAN PSIKOEDUKASI KELUARGA DALAM MENSTIMULASI PERKEMBANGAN ASPEK BIOLOGIS, KOGNITIF DAN BAHASA REMAJA - Hasanah, Uswatun; Reliani, Reliani (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Development in adolescence is often associated with a period full of challenge. Therefore, an adolescent is required to complete the task of self-identity development in order to be able to achieve satisfaction, to reach happiness, and to have a positive identity. The purpose of this paper was to describe a comparison of improvement aspects of adolescents’ self-identity development between adolescents who received therapeutic group therapy and those who received therapeutic group therapy and family psychoeducation. Therapeutic group therapy is a mental health nursing specialist therapy that can improve potential and develop quality among group members in overcoming health problems. The family psychoeducation was given to increase knowledge and ability of family in stimulating adolescents’ identity achievement. The clients consisted of four adolescents with the age range 13-14 years old, two adolescents received therapy of therapeutic group only, while the other two adolescents received therapy of therapeutic group and family psychoeducation. The evaluation results indicated an increase in aspect and task of adolescents' development with maximum attainment value in adolescents who had been given the therapeutic group therapy and family psychoeducation. The analysis process was done by using Stuart and King Adaptation stress model approach. This case report is used as recommendation to provide standard in the mental health nursing specialist’s therapy, to be socialized, and to be carried out in community mental health services. Keywords: Self-Identity, Adolescent, Family Psychoeducation, King Theory